Compact Multi-Element Ultrasonic Transducer for Inspecting Split Pins in Nuclear Power Plants - Guanbing, Ma; Hui, Ding; Weiqiang, Wang; Chao, Ma; Jingli, Yan; Chuanyu, Zhu; Jianbang, Tang (Frontiers in Materials, 2021)
A compact five-element integrated ultrasonic transducer was designed and manufactured for the inspection of defects in the split pins of control rod guide tubes in nuclear power plants. The transducer consists of three types of ultrasonic elements to detect cracks in the entire volume of the split pins. In the transducer design, two main factors were investigated: the coupling of elements in confined space and measurement sensitivity. The experimental results demonstrated that the developed transducer has good acoustic performance and defect response capabilities and can detect 10 mm × 2 mm notches in the three areas of the split pins. This work provides a foundation for applications in nuclear site inspections.